2008
DOI: 10.1590/s0021-75572008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Participação do pai no processo da amamentação: vivências, conhecimentos, comportamentos e sentimentos

Abstract: Objective: To identify the experiences, knowledge, behaviors and emotions of fathers with relation to the process of breastfeeding.Methods: This is a descriptive, explorative and qualitative study involving 17 couples resident in a favela in the city of Recife, PE, in the Northeast of Brazil, whose most recent child was aged between 6 and 8 months. A semi-structured interview employing leading questions was used for data collection. These data were analyzed in the light of theoretical references, the historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
5
0
10
Order By: Relevance
“…In addition, this author evidenced that mothers allocated more resources to buy foods than fathers. Likewise, couples living in the Northeast region of Brazil also indicated that fathers are responsible for the family's economic issues, whereas food care is attributed to mothers 20 . Considering these circumstances, the fact that the biological mother does not live in the home, as observed in the present study, indicates a vulnerable situation involving the child's inadequate nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this author evidenced that mothers allocated more resources to buy foods than fathers. Likewise, couples living in the Northeast region of Brazil also indicated that fathers are responsible for the family's economic issues, whereas food care is attributed to mothers 20 . Considering these circumstances, the fact that the biological mother does not live in the home, as observed in the present study, indicates a vulnerable situation involving the child's inadequate nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Essa introdução diminui a proteção do leite materno contra processos infecciosos, assim como a duração do aleitamento materno (MASCARENHAS et al, 2006). O marido exerce influência positiva na prática do aleitamento materno (PONTES et al, 2008), pois a mulher leva em consideração o que os maridos ou parceiros dizem, e assim motivam e encorajam-nas a amamentar.…”
Section: Apoio Familiarunclassified
“…Grandmothers also have an important role in supporting and encouraging breastfeeding when they consider breast milk an essential food for the health and development of the baby. Nonetheless, grandmothers often lead breastfeeding women to doubt that breast milk is capable of meeting all the nutritional needs of the child 16,17 .…”
Section: Discussionmentioning
confidence: 99%